An alternative to FaaS cold start latency of low request frequency applications - Santos, P.; Costa, H.; Valderi Leithardt; Ferreira, P. (Proceedings of the International Conference on Electrical, Computer, Communications and Mechatronics Engineering (ICECCME 2023), 2023)
—Serverless applications are those that do not require the developer to provide or manage any servers. The developer can focus on core product logic and development and just release their code into a container at the service provider. However, when initializing a container there may be a latency called cold start. This article aims to use the Node.js language as an alternative to the Java language as a prevention against the cold start scenario in applications that have a low frequency of use. With the development of lambda functions with the same functionality in both languages. Noting that the node.js language had an 82% reduction in startup time compared to java.